Next, the coming era in science - Noble, Holcomb B. (Little, 1988)
A collection of nine provocative essays assessing science and technology as they will most certainly develop into the 21st century. Written mostly by science writers and journalists, these essays probe a variety of issues, including artificial intelligence, supercomputers, the "biochip," telecommunications, manmade satellites, space exploration, and cosmology. Not highly speculative fantasies of a distant future, the essays are instead reliable in detail, intelligently written, and directed to the lay reader.